Islamic bank spin-off: a systematic literature review - Mahmud Yusuf; Muhamad Rahmani Abduh; Hafiez Sofyani (Universitas Muhammadiyah Yogyakarta, Indonesia, 2023)
Research aims: This study aims to explore the extent of studies related to Islamic bank spin-offs in reputable journals indexed by Sinta and Scopus to map important findings regarding Islamic bank spin-offs.Design/Methodology/Approach: This study employed a systematic literature review method consisting of three stages: collection, assessment, and presentation. The collection stage was conducted using the Publish or Perish search engine with the Google Scholar and Scopus databases. The assessment stage was performed using the websites https://sinta.kemdikbud.go.id and https://www.scimagojr.com/. The presentation stage was carried out to find three objectives: research background, methods, and findings related to the Islamic bank spin-off.Research findings: Since 2010, at least 24 papers indexed by Sinta and ten papers indexed by Scopus have discussed the issue of the Islamic bank spin-off. These studies were oriented toward two disciplines: law and economics. The most widely used method was quantitative. Broadly speaking, the findings from the spin-off study of Islamic banks can be generalized into four discourses: policy, the market for Islamic banks, performance/efficiency of Islamic banks, and several other matters. Lastly, from the four discourses above, the authors suggest eight future studies that are still interesting to study.Theoretical contribution/Originality: By mapping important findings related to the Islamic bank spin-off along with eight suggested future studies, this research’s results are expected to be a reference and inspiration for scholars in conducting further research related to the Islamic bank spin-off.